The Influence of Auditor Ethics and Auditor Experience on Company Financial Reports - Mediawati, Elis (International Journal of Business, Law, and Education, 2023)
This research investigates the influence of auditor ethics and auditor experience on the quality of financial reports in the garment sector of West Java, Indonesia. This study employs a quantitative approach to measure auditor ethics and experience, utilizing statistical tools for analysis. The research targets financial auditors in Indonesia, with a sample size of 150 auditors selected purposively based on specific criteria.The study emphasizes the importance of auditors in ensuring the accuracy and reliability of financial information. The garment industry in West Java holds significance in Indonesia's manufacturing sector, particularly in terms of employment and export revenue. The research aims to contribute to the understanding of how auditor ethics and experience impact financial reporting quality in this specific industry.